Pariwisata Pelabuhan Ratu Jawa Barat Dilihat Dari Aspek Lingkungan Hidup - Sri Sunarti (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2019)
Tourism is one of the sources of foreign exchange, and so with the tourism of Pelabuhan Ratu beach which one of the revenue resources (PAD) of Suka Bumi regency. In the development of tourism destination object, Pelabuhan Ratu also determined by the environment aspect.In this research, method of research that used is an observation method. While the resource of the data derived from primer and secondary data. The primary data obtained from the local government sources. While the secondary data obtained from the literature or books and scientific journals. Based on the result of the research about the role of environment aspects, in order to preserve the environmental sustainability of Pelabuhan Ratu beach itself, so the development of tourism in Pelabuhan Ratu can be one of the sustainable development that can be approve continuously carried out in every time. One of the effort that can be done by the government in the development of Pelabuhan Ratu based on environment aspects is to determine the tourism development policy in accordance with the environment management which defined in national intermediate development planning.